Effectiveness of the BANI Binding Opinion in the Resolution of Construction Contract Interpretation Disputes: A Case Study of the Kalimantan Steam Power Plant (2x5 MW) Project - Anrizal, Anrizal; Aprianto, Agung; Baharuddin, Ifdal; Lapasau, Ronald; Hardjomuljadi, Sarwono; Sami’an, S. (CV. Social Politic Genius (SIGn), 2025)
Construction disputes in Indonesia are often rooted in differences in the interpretation of contract clauses. This is reflected in the dispute between PT PLN (Persero) and PT XXX over the Kalimantan Steam Power Plant (2x5 MW) development project, regarding claims for an extension of time and additional cost compensation due to social access obstacles. This research aims to conduct a juridical analysis of problems in the interpretation of contract clauses. Additionally, this research constructs the legal basis for granting EoT and real cost compensation, and evaluates the effectiveness and executive power of the BANI Binding Opinion as an instrument of legal certainty. The research method used is normative juridical, through the statute and case approaches to the BANI Binding Opinion Number: XX/BO-BANI/2017 document, and the conceptual approach. The research results reveal that the interpretational deadlock was triggered by the parties’ failure to reach an agreement regarding the allocation of external obstacle risks beyond the contractor’s control. Therefore, BANI determined that a time extension and cost compensation should be granted using the actual implementation cost difference method, based on the principles of propriety and contractual justice, to restore the service provider’s economic position. It is concluded that the BANI Binding Opinion is a highly effective, efficient dispute resolution solution, and possesses stable executive power as regulated in Article 52 and Article 53 of Law Number 30 of 1999. This instrument provides the parties with final and binding legal certainty. This mechanism also mitigates the risk of project termination by registering the decision at the district court without going through an adversarial adjudication process.